(untitled) (International Journal of Engineering and Computer Science, 2017)
Management of maintainability of software in Software Product Lines is still a problematic area. As its very important quality attribute, there has to be a comprehensive basis for assessing and improving it. Several quality models have been proposed to quantify the maintainability. Nevertheless, existing approaches are not activity based. We have proposed a set of activities and set of facts to calculate maintainability in SPL (Software Product Lines) environment. Facts would have a cascaded effect on activities which in turn would have an effect on the sub-factors of maintainability. We have conceptualized the set of activities and facts in the form of an activity based model.